THE IMPLEMENTATION OF DESCRIBING PICTURES STRATEGY ON SPEAKING ABILITY OF JUNIOR HIGH SCHOOL STUDENT - Nia Margaretha; Mai Zuniati; Umar Alfaruq A. Hasyim (Universitas Wiralodra, 2023)
ABSTRACT The problems that hinder students from learning to speak English area lack of vocabulary, pronunciation, grammar, and interest. The aim of this study is to find out speaking ability and the implementation of describing pictures strategy. This research was a case study that obtained data from the English teacher and students in grade 8 of MTs (Islamic Junior High School) Ma’arif Roudlotut Tholibin Metro Lampung. In addition, the data were analyzed by using interactive data analysis namely data reduction, data presentation, and conclusion. The results found that the student’s speaking abilityneeds to be guided and improved. Thus, describing pictures strategy was implemented to guide and improve students’ speaking abilities especially in increasing vocabulary, and improving pronunciation, grammar, and interest. The essential finding lies in assisting the activity given by the teacher to the students in each stage of the strategy. This research implies that assisting students in learning English could lead to better results for the students. The teacher obtains analternative learning strategy in teaching speaking. Moreover, the students can improve their speaking ability.In addition,this research suggests further investigation in terms of examining this strategy to another language aspect so that more comprehensive results will be achieved.